Manajemen Laboratorium Komputer Di Sekolah Menegah Kejuruan Islam - Eka Yulianta (PT Ilmu Data Indonesia, 2024)
Laboratory management is an important component in determining the success of the educational process and one of the factors in improving the quality of education in Indonesia. The importance of computer laboratory management makes every educational institution make maximum efforts to meet computer laboratory management standards to improve the quality of the learning process.This research uses a qualitative approach with descriptive analysis. The subjects of the study were the principal, the head of the sarpras section and the head of the computer laboratory. The data collection techniques used are interview methods, observation methods, and documentation methods, which will later be obtained primary and secondary data to be analyzed together for conclusions. Based on the results of the research that the author has done, it can be concluded that the management of the computer laboratory at SMK Islam Moyudan in supporting the learning process is quite good. However, some computer laboratory management has not been realized, including in the process of planning, organizing, maintaining, and supervising computer laboratory infrastructure. The obstacles experienced are the lack of human resources in the field of administration and infrastructure as well as incoming funds for the procurement process and infrastructure management process that is still slow.